Supervisor support, work environment, work life-balance and employee retention / Ahmad Aqmal Shaiful Kharidan - Shaiful Kharidan, Ahmad Aqmal (Faculty of Business and Management, 2019)
The purpose of this research was to analyze the impact of supervisor support, work environment and work-life balance on the employee retention which take place at Malaysian Qualifications Agency in Cyberjaya. This research is a quantitative research which had used the self-administered electronic questionnaire as the instrument for the collection of data. The data was collected and achieved a percentage of 72.04% out of the possible 250 questionnaires distributed which was derived from the total population of 340 employees who work in Malaysian Qualifications Agency. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) Version 24 Software. The result of this study indicates that two variables (work environment and work-life balance) has positive and significant relationship with employee retention while one variable (supervisor support) has a negative significant relationship with employee retention.